The rising gap between rich and poor: A look at the persistence of educational disparities in the United States and why we should worry - Flores, Roseanne (Cogent social sciences, 2017)
In 2001 the no child left behind act was signed into law with the promise to close the achievement gap between disadvantaged children and their white and more affluent peers. Ribbons were cut, ceremonies were held, as America set off on a new path to ensure that all children would have the tools necessary to achieve the American Dream. Children who in the past only had access to low-quality schools would now be able to attend high-quality schools and acquire the skills necessary to become productive citizens and obtain jobs that would catapult them into the middle class. They would have a “choice.” The choice to attend a failing school, usually deemed “public” or the choice to attend a “charter school” the new option, which would provide them with a high-quality education. Fast forward and after fourteen years of living with the law the idea of obtaining a good public education has continued to decline while the notion of attending a high-quality charter school has continued to be popular in spite of the evidence. The purpose of this paper is to address how neoliberal policies have simultaneously led to the growth of charter schools and the persistence of educational disparities and to examine what is in store for the majority of Americans in the near future if public education destroyed.